2021
DOI: 10.33448/rsd-v10i12.20517
|View full text |Cite
|
Sign up to set email alerts
|

A efetividade do tratamento para dor utilizando auriculoterapia: um artigo de revisão

Abstract: A auriculoterapia, microssistema da acupuntura, constitui-se como um principal método terapêutico em tratamentos de dores. O uso de sua prática dentro da medicina tradicional chinesa é datado a décadas, onde são feitos estímulos em determinadas áreas da orelha, e estes possuem reflexos no corpo. Este estudo tratou-se de uma pesquisa bibliográfica descritiva que tem por objetivo geral realizar uma revisão literária, onde possa ser identificado como auriculoterapia é utilizada no processo terapêutico de analgesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Although some studies have not found robust scientific evidence (ZHENG; YUAN; LIU, 2014) and still claim that acupuncture could be a placebo treatment, many authors have conducted research, including randomized controlled trials, and found improvements in patients (KUREBAYASHI et al, 2017;SMITH et al, 2007;MILLER et al, 2011;GAVRONSKY et al, 2012;KATANA et al, 2018). At the same time, literature reviews (SANTOS et al, 2021;FINKLER;MARTIM, 2019;ZHANG et al, 2013) and meta-analyses (MANHELMER et al, 2005;VICKERS et al, 2012) have been published., demonstrating the efficacy of treatments with acupuncture and auriculotherapy for pain, especially chronic pain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies have not found robust scientific evidence (ZHENG; YUAN; LIU, 2014) and still claim that acupuncture could be a placebo treatment, many authors have conducted research, including randomized controlled trials, and found improvements in patients (KUREBAYASHI et al, 2017;SMITH et al, 2007;MILLER et al, 2011;GAVRONSKY et al, 2012;KATANA et al, 2018). At the same time, literature reviews (SANTOS et al, 2021;FINKLER;MARTIM, 2019;ZHANG et al, 2013) and meta-analyses (MANHELMER et al, 2005;VICKERS et al, 2012) have been published., demonstrating the efficacy of treatments with acupuncture and auriculotherapy for pain, especially chronic pain.…”
Section: Resultsmentioning
confidence: 99%
“…According to Santos et al (2021), the analgesia that acupuncture provides is due to the stimulation of small-diameter nerves. These nerves, with different thresholds, send messages to the spinal cord, activating gray area and hypothalamus neurons, initiating endogenous opioid mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De acordo com Santos et al (2021), a auriculoterapia é uma técnica da Medicina Tradicional Chinesa (MTC) direcionada a tratamento de doenças tanto físicas como mentais, realizada através de estímulos em pontos localizados no pavilhão auricular. Cada orelha apresenta pontos de reflexos equivalentes a todos os órgãos, bem como a funções do corpo.…”
Section: Intervenções Da Terapia Ocupacionalunclassified